Synthesized-reference-wave holography for determining antenna radiation characteristics - Schejbal, Vladimír; Kovařík, Vlastimil; Čermák, Dušan (IEEE, 2008)
Synthesized-reference-wave holographic techniques offer relatively simple and cost-effective measurement of antenna radiation characteristics and reconstruction of complex aperture fields using near-field intensity (power) pattern measurement. The near field is over-sampled. The phase is obtained indirectly, using the reference signal shifted linearly with the position of the probe. These methods allow utilization of advantages for probe compensation for near-field amplitude and phase measurements for planar and cylindrical scanning, including accuracy analyses. Descriptions are given of holographic near- field measurements using probe compensation for planar and cylindrical scanning, and numerical simulations. A comparison of holographic near-field and far-field measurements with and without probe compensation is presented.
Keywords: antenna measurement; antenna radiation patterns; near-field sampling; near-field measurements; antenna probe compensation; holography